Philosophical Underpinnings of Nature Poetry: Wordsworthian Romanticism vs. Frostian Realism (Journal of Advances and Scholarly Researches in Allied Education, 2023)
One of the first things that we are going to do is examine historical literature that depict the relationship between India and Nepal as being founded on shared sovereignty. In the next section, we will discuss the negative aspects of this discourse that is unfavorable and completely mindless. It is lacking in depth, deceptive, and prone to conforming to stereotypes. It is essential to keep in mind that any historical account that minimizes the relevance of realpolitik is neglecting the narrative of India as a hegemon that interferes in Nepal's internal affairs and impedes the nation's social, economic, and political growth. This is something that must be kept in mind. Several features of Nepal-Indian relations may be traced back to a time before the contemporary nation-state was established. In order to demonstrate how India has violated Nepal's independence and sovereignty from a neocolonial point of view, we provide the facts. The process of globalization has brought forth challenges, hazards, and uncertainties in relation to the movement of people, products, and money. As a consequence of this, border governance between states has been established, which necessitates the aid of surrounding countries in the development of border management systems. Within the context of the "practice turn" in international relations (IR), this qualitative research investigated the ways in which conduct influences social reality. Over the course of this historical period, the open border that divided India and Nepal was the primary focus of the inquiry. The findings of the analysis indicate that the open border that exists between India and Nepal poses a wide range of hazards and challenges that are not found anywhere else. Based on the findings of the research, a concise definition of border relations management was provided. Furthermore, it includes a proposition for the management of Nepal's open borders with India, as well as an explanation of the concepts and techniques behind the proposal. Despite the fact that it acknowledged the existence of border conflicts and significant barriers, the study concentrated primarily on the subject of border governance for the boundaries that separate Nepal and India.